Gambaran Tingkat Kesiapsiagaan Masyarakat Menghadapi Bencana Tanah Longsor di Dukuh Secang Sambirejo - Della Anggelia Septiani; Hermawati Hermawati (Calory Journal Medical Laboratory Journal, 2026)
Background: Sambirejo is prone to landslides due to steep slopes and heavy rainfall, but community preparedness remains low due to limited awareness campaigns, the absence of emergency response teams, minimal reforestation, and a lack of knowledge about local disaster evacuation procedures. Objective: To determine the preparedness of residents in facing landslides in Dukuh Secang. Method: The method used was a direct survey with a sample size of 57 respondents and used Non- probability Sampling with the Purposive method. Results: The study shows that based on the characteristics of the respondents, the majority are young adults aged 26-35 years (26.3%), the majority are female with 33 respondents (57.9%), and the majority have a high school education (43.9%). The overall results indicate that the preparedness of residents in Dukuh Secang Jetis Sambirejo Sragen is in the “Very Prepared” category. The preparedness indicators showed a high level of knowledge (64.9%), policies and guidelines (94.7%), emergency plans (94.7%), warning systems (94.7%), and resource mobilization (91.2%). Conclusion: The preparedness of residents in facing landslides in Dukuh Secang, Jetis Sambirejo Village, Sragen is in the very ready category with a preparedness index score of 78.9%.